Non‐motor symptoms in patients with autosomal dominant spinocerebellar ataxia. (5th August 2020) - Mastammanavar, Vinayakumar S.; Kamble, Nitish; Yadav, Ravi; M, Netravathi; Jain, Sanjeev; Kumar, Keshav; Pal, Pramod Kumar
Abstract: Objective: The non‐motor manifestations of motor predominant disorders have been an area of active interest in recent times. The objective of the study was to determine the prevalence of non‐motor symptoms in patients with genetically confirmed spinocerebellar ataxia (SCA). Materials and Methods: Forty‐one patients of SCA and 48 age‐, gender‐, and education‐matched controls were included. The severity of ataxia was evaluated using the International Cooperative Ataxia Rating Scale (ICARS) and cognitive impairment using a neuropsychological battery. Non‐motor features were assessed using standardized scales (HAM‐A, HAM‐D, Modified Fatigue Severity Scale, RLS questionnaire, ESS, PSQI, WHOQOL, RBDSQ, and BPI). The data were compared with controls and correlated with the severity of ataxia. Results: There were 17 SCA1, 14 SCA2, and 10 SCA3 patients. The mean age of presentation was 35.7 ± 7.9 years for SCA1, 31.1 ± 7.9 years for SCA2, and 30.5 ± 9.5 years for SCA3 patients. The neuropsychological evaluation showed severe impairment of attention, executive functions, visuospatial function, motor speed, response speed, and memory. The severity of ataxia was more for SCA2 patients (ICARS of 39.5 ± 24.4). Ataxia severity was correlated with MMSE, fatigue scale, depression scale, and REM sleep behavior disorder in SCA1 individuals and global cognition, fatigue, anxiety, and depression scales, and RLS in SCA3 patients. All patients reported quality of life as dissatisfied. These patients also had sleep disturbances in the form of RBD, RLS, and EDS. Conclusions: In addition to the motor symptoms, patients with SCA have several non‐motor symptoms that impair the quality of life.